Discrete or not so discrete: long distance movements by coastal bottlenose dolphins in UK and Irish waters - Robinson, Kevin P.; O'Brien, Joanne M.; Berrow, Simon D.; Cheney, Barbara; Costa, Marina; Eisfeld, Sonja M.; Haberlin, Damien; Mandleberg, Laura; O'Donovan, Mairead; Oudejans, Machiel G.; Ryan, Conor; Stevick, Peter T.; et al. (J. Cetacean Res. Manage., 2023)
The potential for long distance movements in common bottlenose dolphins (Tursiops truncatus) from six UK and Irish study sites was examined using photographs of natural markings. Here we provide the first evidence for long-term re-sightings between the Moray Firth, Inner Hebrides and across international borders to the Republic of Ireland as determined for eight individuals over a ten year period from 2001 to 2010. Minimum dispersal distances of up to 1,277km were resolved providing a new distance record for the species in European waters. Although none of the sightings were made within protected areas, several were made in waters used by animals from a Special Area of Conservation (SAC) revealing some evidence for connectivity between areas previously regarded as discrete. Our findings highlight the need to mitigate broader-scale anthropogenic impacts affecting these dolphins across multiple sites throughout their coastal range. Accordingly, we underline the importance of developing wider conservation measures for this species in UK and Irish waters, but particularly in prospective corridor areas potentially linking designated SACs in the Moray Firth, Cardigan Bay and Shannon Estuary.